(3ebOeI aj GdeMGSHI GdeGdjI habG deYGjjQ GdeMGSHI GdeUQjI h GdOhdjI (B/s - (3HOhj , eMeO YHGSs; (3YKeGf, GdCejQI EHQGgjes; (3Ydj, YHO GdhgGH fUQ s ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2006)
(3GdeMGSHI Yf YedjGJ JUfjY GdefJL , hhQbI GdYed h GdbhGFe GdeGdjI ddeTQhY GdUfGYj h LQO h JShjI cd ef GdfbOjI h ChQGb GdbHV h GdYedGA h GdeNRhf h LQO GdCUhd GdKGHJI h LQO h JShjI GdNUhe h cPG JfGhd GdjhejGJ GdeSGYOI h GdMSGHGJ GdGLeGdjI h CNjQG GdCNWGA GdeMGSHjI h cjajI eYGdLJgG(B.s
Keywords: (3GdeGdjI GdYGeIs; (3GdeMGSHI GdJMdjdjIs